The Effectiveness of Using Song Lyrics Containing Degrees of Comparison to Improve Students' Grammar Mastery - Maria Maria; Septian Dwi Putri; Dina Juniar Anggraini (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the effectiveness of using song lyrics containing Degrees of Comparison to improve students’ grammar mastery. A quantitative approach with a quasi-experimental pre-test–post-test control group design was employed. The experimental class received instruction using song lyrics, while the control class received conventional instruction. Data were collected through tests, observations, and documentation and analyzed using descriptive statistics, t-tests, normalized gain, and Cohen’s d. Based on the simulated data, the experimental class mean score increased from 56.70 to 76.10, while the control class increased from 57.10 to 65.93. The post-test difference between the groups was significant at p < 0.001. Cohen’s d value of 1.277 indicated a large effect. These findings suggest that song lyrics have the potential to improve students’ mastery of Degrees of Comparison. However, field-based research is still required because the results were generated from simulated data.